2020
DOI: 10.3892/ol.2020.11660
|View full text |Cite|
|
Sign up to set email alerts
|

Rab5 regulates the proliferation, migration and invasion of glioma cells via cyclin E

Abstract: Glioma is the most common and lethal type of primary brain tumor, with a high mortality and recurrence rate. Rab5, which serves as a classic ontogenetic gene, is highly expressed in various types of tumor, including lung cancer, hepatocellular carcinoma and ovarian cancer. However, the exact role and the underlying mechanism of Rab5 in glioma remain unknown. Herein, the role of Rab5 in the tumorigenesis and metastasis of glioma cells was investigated. The upregulation of Rab5 in glioma tissues and cells was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…TBC1D3H belongs to TBC1 domain family, which can act as a GTPase activating protein for RAB5 ( Itoh et al, 2006 ; UniProt, 2021 ). Its dysregulation can lead to tumorigenesis ( Jian et al, 2020 ). Other proteins with TBC1 domain also function in cancer; for instance, TBC1 domain family member 23 can interact with Ras-related protein Rab-11A to promote poor prognosis in lung cancer ( Zhang et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…TBC1D3H belongs to TBC1 domain family, which can act as a GTPase activating protein for RAB5 ( Itoh et al, 2006 ; UniProt, 2021 ). Its dysregulation can lead to tumorigenesis ( Jian et al, 2020 ). Other proteins with TBC1 domain also function in cancer; for instance, TBC1 domain family member 23 can interact with Ras-related protein Rab-11A to promote poor prognosis in lung cancer ( Zhang et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…These observations suggest a mechanism that the Rab5-GEF, Rabex-5, is recruited to the TGN by GGAs and promotes cargo transport from the TGN to the early endosome via GGA vesicles. Human Rab5 and Rabex-5 have been reported to be upregulated and promote the metastasis ability in several types of malignant tumor cells (Jian et al, 2020; Wang et al, 2014). Intriguingly, mammalian RAB11, ARF1, and PI4KIIIβ (homologues for Arf1p, Rab11 and Pik1p) are also upregulated in these tumor cells (Ferro et al, 2021; Gu et al, 2017; Morrow et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The role of Rab5 in glioma progression and resistance to anti-EGFR therapy is still a matter of debate. Indeed, a recent study reported that in humans, Rab5 is overexpressed in glioma tissue compared to normal brain and that overexpression of Rab5 leads to enhanced proliferation and migration, which can be reversed by knockout of Rab5 [48]. By contrast, it has been shown that Rab5 inhibition sustains aberrant oncogenic EGFR signalling.…”
Section: Discussionmentioning
confidence: 99%